An extracellular steric seeding mechanism for Eph-ephrin signalling platform assembly - Seiradake, Elena (2010)
Erythropoetin-producing hepatoma (Eph) receptors are cell surface protein tyrosine kinases mediating cell-cell communication. Upon activation they form signalling clusters. We report crystal structures of the full ectodomain of human EphA2 (eEphA2), alone and in complex with the receptor-binding domain of the ligand ephrinA5 (ephrinA5(RBD)). Unliganded eEphA2 forms linear arrays of staggered parallel receptors involving two patches of residues conserved across A-class Ephs. eEphA2-ephrinA5(RBD) forms a more elaborate assembly, whose interfaces include the same conserved regions on eEphA2, but re-arranged to accommodate ephrinA5(RBD). Cell surface expression of mutant EphA2s demonstrated that these interfaces are critical for localization at cell-cell contacts and activation-dependent degradation. Our results suggest a ‘nucleation’ mechanism whereby a limited number of ligand-receptor interactions seed an arrangement of receptors which can propagate into extended signalling arrays.